Microorganismos más frecuentes en hemocultivos del servicio de Neonatología. Hospital General Docente Ambato. mayo 2017-junio 2018 - Zamora Paucar, Leonela Lissette (2018)
It was made a positive case study was conducted in samples of blood cultures in the neonatology service of the Hospital General Docente "Ambato during the year 2018. The objective of this research was to identify the most frequently detected infectious microorganisms in blood cultures from the neonatal service according to the hospital's statistical data. The methodology that was carried out in this study was statistically descriptive, retrospective, transversal and of a quantum-qualitative nature. Data collection and analysis techniques and instruments were used as a report of laboratory results and statistical programs. Among the results obtained were identified as the most frequent microorganisms in the blood cultures of the neonates with sepsis to Staphylococcus epidermidis and Staphylococcus aureus and among the main risk factors involved in the development of Sepsis were found: gestational age greater than 37 weeks (66.67%), male sex (64.10%), and weight greater than 2,500 grams (71.79%). In relation to antimicrobial resistance and susceptibility S. Epidermidis and S. aureus were highly resistant to oxacillin (61.5%), clindamycin (61.5%), erythromycin (100%) and ciprofloxacin (53.8%) and were sensitive to linezolid and vancomycin in the same Percentage (84.6%), it is also important to note that 61.5% of these strains expressed fenoticamente the gene MecA. These results make it possible to conclude that adequate control of risk factors in newborn infants can ensure a decrease in the occurrence of neonatal sepsis in particular and improve the quality of life of infants